Proposta de técnica de controle indireto da tensão nos terminais do arranjo fotovoltaico para seguimento do ponto de máxima potência utilizando reduzido número de sensores - Freitas, Pedro Augusto Ramos de (2024)
This study aims for advancements in the photovoltaic energy sector, as it proposes a topology of a single-phase inverter with a new GMPPT (Global Maximum Power Point Tracking) control strategy through the sensing of the current injected into the grid. The main contributions of this research pertain to the reduction and simplification of the power circuit and control logic, given that it is limited to monitoring the time during which the switches of the inverter’s high-frequency arm remain closed. This closed switch time is directly associated with the on grid current and indirectly associated with DC bus voltage, serving as an indicator for implementing the proposed GMPPT technique. Experimental and simulation tests were conducted under different irradiance and temperature conditions, which are primary parameters for photovoltaic energy generation capacity, as well as under their transient conditions. The majority of results were satisfactory, indicating a tracking factor exceeding 99% under steady state condition, thus validating the efficiency of our proposal.